The Influence of Startup Development and The Use of Accounting Information Systems on Business Decisions for Accounting Students - Natalia, Susan; Puspita, Erna; Winarko, Sigit Puji (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research aim : The purpose of this research is to see how much influence the development of startups and the use of accounting information systems have on business decisions for accounting students. Design/Method/Approach : The research method used is quantitative with an associative approach. The sample collection used the purposive sampling method which has criteria namely accounting students at the Nusantara PGRI Kediri University who must have received courses in accounting information systems and entrepreneurship. The total population is 174 students while the sample obtained is only 121 sources. Samples were collected by distributing questionnaires to informants using the Google form with statements that had been tested for validity and reliability. To test the hypothesis using multiple linear regression tests through the SPSS application. Research Finding : The results of this study state that business decisions for accounting students are strongly influenced by the development of startups and the use of accounting information systems. Theoretical contribution/Originality : - Practitionel/Policy implication : - Research limitation : -